Assessment of self‐/parent‐reported quality of life in Japanese children with haemophilia using the Japanese version of KIDSCREEN‐52. Issue 2 (24th February 2020) - Furuichi, Yasuko; Nogami, Keiji; Yada, Koji; Nezu, Satoko; Obayashi, Kenji; Saeki, Keigo; Kurumatani, Norio; Nakajima, Mitsuru; Kinoshita, Seiji; Shima, Midori
Abstract: Introduction: Assessing health‐related quality of life (HRQOL) is critical for providing comprehensive clinical care to patients with haemophilia. HRQOL in individuals with similar cultural backgrounds should be compared using internationally standardized, generic questionnaires. Aim: To evaluate self‐/parent‐assessed HRQOL in Japanese children and adolescents with haemophilia A or B. Methods: Children and adolescents aged 8‐18 years were enrolled. The haemophilia group comprised families with haemophilia, and the control group comprised those without chronic illness. HRQOL was assessed using the self‐/parent‐reported questionnaire KIDSCREEN‐52, the Japanese version. The Oslo 3‐Item Social Support Scale was investigated. Results: The questionnaire was completed by 36 families in the haemophilia group and 160 parents and children in the control group. Haemophilia children aged 8‐12 years had lower scores for 'moods and emotions' than control children; the parents had lower scores in the haemophilia group than in the control group for 'moods and emotions', 'social support and peers', and 'school environment'. No significant differences in HRQOL were observed between both groups of adolescents aged 13‐18 years or their parents. Neck‐shoulder pain was associated with a low psychological state, including 'self‐perception', but other joint pains did not affect the outcomes of the HRQOL indices. Social support weaknesses were associated with low physical and psychological states, whereas unexpected hospital visits identified low values for 'self‐perception', 'autonomy', and 'school environment'. Conclusion: Proactive mental and clinical care in haemophilia families, especially with young children, will foster a better environment for patients and their parents and ease concerns about progress in haemophilia.